Introduction to emergency management / George D. Haddow, Jane A. Bullock, Damon P. Coppola. - Haddow, George D.; Bullock, Jane A.; Coppola, Damon P. (UK: Elsevier, 2021)
This long-trusted resource provides a broad overview of the key aspects of the emergency management profession. Readers will gain an understanding of why the emergency management profession exists, what actions its professionals and practitioners are tasked with performing, and what achievements are sought through the conduct of these various efforts. Students and new professionals alike will further gain an enhanced understanding of key terminology and concepts that enable them to work with emergency management specialists.
Previous edition: 2017.
Includes bibliographical references (pages 487-504) and index.
Keywords: Emergency management; Society; Emergency management; Society